The Comparative Analysis of The Financial Performance of PT Pertamina Geothermal Energy Tbk Before and After Initial Public Offering - Riko Mersandro Permana; Satria Chandra (Lembaga Intelektual Muda (LIM) Maluku, 2024)
This study aims to compare PT Pertamina Geothermal Energy Tbk (PGEO) financial performance in conditions before and after the Initial Public Offering (IPO). The method used in this study is a descriptive research method with a quantitative approach, using secondary data, namely the Corporate Financial Report 2020-2023. Measuring a company's financial performance uses the liquidity ratio, activity ratio, solvency ratio, and profitability ratio. The results of the study indicate that the company's performance tends to be better after the IPO compared to the performance before the IPO, both in terms of liquidity, activity, solvency, and profitability.